THE UNITS HAVE BEEN SIMPLIFIED BASED ON PHONETIC CHANGES - Usmanova Mokhira Kenjayevna (Journal Park Publishing, 2023)
The article discusses the study of the change in the composition of the word morpheme - the phenomenon of simplification. It is shown that the simplified units of the Uzbek language were created on the basis of various phonetic changes. The phonetic structure of the current Uzbek dictionary has become more complex, it has changed from monosyllabic to polysyllabic, but the morpheme structure has been simplified (integrated, for various reasons, it has been additionally assimilated with the base the structural-semantic, phonetic-derivative development of words is revealed. The reasons for the phonetic structure of monosyllabic root words to acquire polysyllabic phonetic structures are based on the historical development process.
Keywords: simplification, base, affix, complex component, root, phonetic structure, morpheme, sound exchange, semantics, root word, etymological analysis, emotional expression.